STRESS LEVEL DESCRIPTION IN PATIENTS WITH DYSPEPSIA SYNDROME IN THE EMERGENCY OF PAKUHAJI REGENCY, TANGERANG REGENCY (Jurnal Kesehatan STIKes IMC Bintaro, 2025)
Background: Dyspepsia is a collection of symptoms associated with upper digestive tract disorders and is often associated with stress levels. At Pakuhaji Regional Hospital, the number of patients with dyspepsia syndrome shows an increase, Research Objective: to describe the level of stress in patients with dyspepsia syndrome in emergency room at Pakuhaji Regional Hospital,Tangerang Regency. Method: This research used a descriptive analytical design which was carried out in the Emergency Room (IGD) of Pakuhaji Regional Hospital in June-July 2024. A total of 96 respondents who were diagnosed with dyspepsia syndrome were the subjects of this research. Data was collected through a questionnaire that measured the level of stress and severity of dyspepsia syndrome. Results: The results showed that the majority of respondents experienced mild stress (52.1%), moderate stress (41.7%) and severe stress (6.3%). Most respondents also experienced dyspepsia syndrome with moderate (47.9%) and mild (43.8%) severity. Conclusion and Suggestions: There is a relationship between stress levels and the severity of dyspepsia syndrome in patients in the IGD at Pakuhaji Regional Hospital. It is hopedthat the hospital can provide education on managing sress levels using flyers and can reduce the incidence of dyspepsia syndrome.